2020
DOI: 10.1177/0885328220942906
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of piezoelectric porous BaTiO3 scaffold to repair large segmental bone defect in sheep

Abstract: Porous titanium scaffolds can provide sufficient mechanical support and bone growth space for large segmental bone defect repair. However, they fail to restore the physiological environment of bone tissue. Barium titanate (BaTiO3) is considered a smart material that can produce an electric field in response to dynamic force. Low-intensity pulsed ultrasound stimulation (LIPUS), as a kind of micromechanical wave, can not only promote bone repair but also induce BaTiO3 to generate an electric field. In our studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…This stimulus can make the bone tissue itself produce the piezoelectric effect, change the internal potential of bone tissue, and thus stimulate bone formation. 25…”
Section: Discussionmentioning
confidence: 99%
“…This stimulus can make the bone tissue itself produce the piezoelectric effect, change the internal potential of bone tissue, and thus stimulate bone formation. 25…”
Section: Discussionmentioning
confidence: 99%
“…The above parameters are critical for bone tissue formation. In our previous study, , we prepared pTi/BaTiO 3 scaffolds and applied them to the study of large bone defects in sheep and rabbits and achieved good bone repair results. In this study, we used the same technique to prepare interbody fusion cages for anterior cervical discectomy and fusion in sheep.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the preparation of BaTiO 3 implants with personalized and precise spatial configurations presents challenges, mainly because there are challenges in processing and formulating the raw material for printing and inducing piezoelectricity . Our previous study showed that a BaTiO 3 coating on a porous a Ti6Al4V scaffold could improve the growth of new bone tissue and improve the repair efficiency of large bone defects in load-bearing areas, , suggesting that combining 3D-printed porous Ti6Al4V with piezoelectric BaTiO 3 is a promising therapeutic strategy for bone defects, such as those obtained by trauma or orthopedic surgery.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, when incorporated in vivo within a load-bearing tissue (such as the OCT-, cartilage-or bone ECM), being subject to native loads produced by skeletal mobility, this material is capable of attracting different cations, such as Ca , Barium titanate, the first lead-free piezoceramic to be developed and the most studied piezoceramic in TE, is highly biocompatible, with several in vitro and in vivo studies reporting their ability to promote cell attachment, cell proliferation, and tissue growth, among other relevant cellular activities [33,42,54]. Multiple studies have also identified the osteoconductive and osteoinductive potential of this bioactive ceramic [42,48,58]. Barium titanate is also characterized by a high Young's modulus (118 GPa) and compressive strength (913.2 MPa) [59].…”
Section: Piezoceramicsmentioning
confidence: 99%